Early Diagnosis of Congenital Malformations During Child Examination by Primary Care Specialists for the Purpose of Differentiating Genetically Determined Dysmorphisms from the Child’s Constitutional Features - Horobets, Аnastasiia; Horobets, Nataliia I.; Horobets, Nataliia М. (The Ukrainian Scientific Medical Youth Journal, 2026)
in the review article analyze contemporary publications on dysmorphisms, which may be of either physiological or pathological origin and represent a relevant issue in modern medicine in the context of the rapid development of orphan diseases. Therefore, this review aims to demonstrate the importance of early diagnosis of congenital malformations during child examination by primary care specialists to differentiate genetically determined dysmorphisms from constitutional features or from alterations in body morphogenesis (of the whole body or its parts) resulting from negative external influences on the fetus. This is highly relevant due to the complexity of early diagnosis and differential diagnosis. Timely identification of pathological features in a child by a primary care specialist will accelerate referral for genetic counselling to verify the diagnosis and will allow for the earliest possible organisation of necessary multidisciplinary preventive, therapeutic, and rehabilitation measures aimed at minimising adverse consequences of the disease and improving the quality of life of both the child and their family. To understand which features are pathological and how to distinguish them from constitutional characteristics or from morphological changes of body parts resulting from negative external influences on the fetus, a method of morphometric assessment of various anatomical regions of the child’s body can be applied using specially developed programs of unified diagnostic methods (Gestalt). According to contemporary publications, these methods help differentiate pathology from physiological variations. Based on current sources, the authors indicate that morphological deviations in child development – manifesting as deformations, associations, disruptions, dysplasias, minor anomalies of development, or stigmata of dysembryogenesis – may result from various influences. However, they are often clinical markers of orphan diseases and indicate the presence of certain genetic syndromes. At the same time, such abnormalities may develop intrauterinely in a fetus in the absence of genetically determined factors, arising instead as a result of the negative influence of external factors. In this regard, early diagnosis and verification of the diagnosis are of vital importance, since the earlier a disease is identified, the sooner the needed preventive, therapeutic, and rehabilitation measures can be initiated to prevent or delay the development of complications and to minimise their negative impact on the child’s condition and life. Clinical assessment of a child by primary care specialists remains the “gold standard” of examination. However, to avoid subjectivity and to conduct a more thorough diagnostic search for pathological deviations in a child’s morphogenesis, it is necessary to apply specially developed objective programs of unified diagnostic methods (Gestalt).